Anti-Alcohol Education in the Secondary Education Curriculum of Nepal (OCEM Journal of Management, Technology & Social Sciences, 2024)
In Nepalese secondary education curriculum, anti-alcohol education has been integrated into the various subjects’ curriculum. For example, the curriculum of some important subjects related to people’s daily and social life (health and physical education, sociology, hotel management, human values education, social studies, science, and technology) includes anti-alcohol education content. However, the extent to which anti-alcohol education is being implemented in these subjects remains unclear. The main objective of this study is to investigate the status and nature of anti-alcohol education in the secondary school curriculum in Nepal. Secondary school curriculum and pedagogy were reviewed for content analysis. This study was based on qualitative content analysis and document review methods. This study found alcohol education content has been included in the curriculum of secondary school subjects (grades 9 to 12) in science and technology, social studies, life skills education, sociology, hotel management, health and physical education, human values education. However, the scope of the alcohol education content included in the Secondary School curriculum seems to be limited. Some subjects’ curricula include alcohol control measures, while others only mention alcohol consumption as a cause of non-communicable diseases. Therefore, it can be said that little attention has been paid to incorporating anti-alcohol education into the secondary school curriculum. Furthermore, among the secondary education curriculum that includes alcohol education, only the science and technology curriculum has recommended particular content delivery techniques(lecture, demonstration, discussion, presentation) and student achievement evaluation techniques(oral questionnaire) for teaching and evaluating students related to the introduction and types of alcohol.